Adoption of Website Technology as a Business Funding Platform for Student MSMEs: Diffusion of Innovation (DOI) Theory Perspective - Utami, Tri Lestari Wahyuning; Anindya, Khoirina Noor; Muzakir, Mellisa Fitri Andriyani; Darmawan, Arief; ., Muzariyantomi; Mansyur, Saddam Murtadho; Rasipu, Muhammad Nur Alim; Nafidien, Nayla Afifah; Helmy, Haikal Hifzhi (Journal of Ecohumanism, 2025)
This study investigates the adoption of GEMAH, a digital platform connecting investors and micro, small, and medium enterprises (MSMEs) owned by students, using the Diffusion of Innovation (DOI) framework. The findings highlight GEMAH’s advantages in providing efficient and accessible funding tailored to the digital preferences of Gen Z entrepreneurs. However, challenges remain in usability and information clarity, which are critical for first-time users. Trialability fosters user confidence, yet a lack of testimonials and case studies limits trust, and the platform’s early development stage constrains observability. Additionally, regulatory and infrastructural gaps underscore the importance of institutional support from universities and financial authorities like OJK. This study suggests improving GEMAH’s features, enhancing transparency, and fostering user trust through regulatory assurance and collaboration with educational institutions. GEMAH holds potential as a sustainable solution for financial inclusion and the growth of student MSMEs in Indonesia.